2021
DOI: 10.2166/wst.2021.194
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae cultivation in wastewater effluent from tilapia culture pond for enhanced bioethanol production

Abstract: The large number of wastewaters are generated because of the various production processes. Vegetable and fish processing can be considered an important industry for wastewater generation. The essential method for completing this waste is to digest the organic matter using anaerobic digestion followed by aerobic wastewater treatment processes; however, wastewater from tilapia culture pond retains considerable quantities of inorganic substances, particularly nutrients like nitrogen and phosphorus. The optimal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“… Onay (2018) demonstrated that bioethanol yields of Nannochloropsis gaditana in various concentrations of municipal wastewaters (0, 30, 60, and 100%) ranging from 70.3 ± 2.4 mg g biomass −1 to 94.3 ± 5.5 mg g biomass −1 and 30% of wastewater showed the highest bioethanol yield (94.3 ± 5.5 mg g −1 biomass). A recent study by Bhuyar et al, 2021 showed that C. vulgaris cultivation in wastewater effluent from tilapia culture pond produced biomass of 0.376 ± 94.21 mg L −1 after cultivation and produced the highest ethanol concentration of 33.213 g L −1 after 96 h of fermentation.…”
Section: Wastewater Integrated Algae-biorefinery For High-value Compo...mentioning
confidence: 98%
“… Onay (2018) demonstrated that bioethanol yields of Nannochloropsis gaditana in various concentrations of municipal wastewaters (0, 30, 60, and 100%) ranging from 70.3 ± 2.4 mg g biomass −1 to 94.3 ± 5.5 mg g biomass −1 and 30% of wastewater showed the highest bioethanol yield (94.3 ± 5.5 mg g −1 biomass). A recent study by Bhuyar et al, 2021 showed that C. vulgaris cultivation in wastewater effluent from tilapia culture pond produced biomass of 0.376 ± 94.21 mg L −1 after cultivation and produced the highest ethanol concentration of 33.213 g L −1 after 96 h of fermentation.…”
Section: Wastewater Integrated Algae-biorefinery For High-value Compo...mentioning
confidence: 98%
“…Owing to the favourable potentiality for the treatment of wastewater, reduction of CO 2 , as well as production of biofuel, biochemical, and biomaterial, microalgae have been of great interest over the last few decades (Srimongkol et al, 2022;Venkata Subhash et al, 2022). Microalgae absorb nutrients such as N and P from wastewater and build up organic compounds intracellularly as they develop photosynthetically utilizing CO 2 as a carbon source (Bhuyar et al, 2021). The high cost of nutrients provided as chemical salts, which is a key problem for large-scale microalgae production, can be reduced by growing microalgae using wastewater (Venkata Subhash et al, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selecting cost-effective and efficient alternative wastewater treatment methods is crucial, particularly in low-income countries. In terms of the total number of facilities, algal-based wastewater treatment systems (e.g., high-rate algal ponds and waste stabilization ponds) are among the most commonly used treatment technologies worldwide [9][10][11][12]. HRAPs have recently been regarded as an appropriate option for wastewater treatment due to their significant advantages over traditional pond systems, including simplicity, lower construction and operation costs, low energy consumption, robustness, and sustainability, as well as the ability to reduce nutrients, micropollutants, and pathogenic microbes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%